Quiet politics of employment protection legislation?: partisan politics, electoral competition, and the regulatory welfare state - Degen, Linda; Zohlnhöfer, Reimut (The annals of the American Academy of Political and Social Science, 2020)
Political parties and party competition have been important factors in the expansion and retrenchment of the fiscal welfare state, but researchers have argued that regulatory welfare is not part of political debate among parties. We explore this claim theoretically, and then empirically examine it in the case of employment protection legislation (EPL) in twenty-one established democracies since 1985. EPL is a mature and potentially salient instrument of the regulatory welfare state that has experienced substantial retrenchment. We test three prominent mechanisms of how electoral competition conditions partisan effects: the composition of Left parties’ electorates, the strength of pro-EPL parties, and the emphasis put on social justice by pro-EPL parties. We find that the partisan politics of EPL is conditioned by electoral competition under only very specific circumstances, namely when blame sharing becomes possible in coalitions between EPL supporters.